Nitrous Oxide Emission Associated with Autotrophic Ammonium Oxidation in Acid Coniferous Forest Soil - Martikainen, Pertti J. (1985)
Aerobic N(2)O production was studied in nitrifying humus from urea-fertilized pine forest soil. Acetylene and nitrapyrin inhibited both NH(4)(+) oxidation and N(2)O production, indicating that N(2)O production was closely associated with autotrophic NH(4)(+) oxidation. N(2)O production was enhanced by low soil pH; it was negligible above pH 4.7. When soil pH decreased from 4.7 to 4.1, the relative amount of N(2)O-N produced from NH(4)(+)-N oxidized increased exponentially to 20%. There was also some evidence that N(2)O formation was stimulated by salts (potassium sulfate and sodium phosphates). The maximum rate of N(2)O-N production was 0.17 μg of N(2)O-N per g of soil per h. When humus was treated with NO(2)(−), N(2)O evolved immediately, indicating chemical formation, but no N(2)O was formed on the addition of NO(3)(−). The amount of N(2)O-N evolved was 0.6 to 4.6% of NO(2)(−)-N added. A high concentration of NO(2)(−) and low soil pH enhanced chemical production of N(2)O. There was no accumulation of NO(2)(−) during nitrification. The calculations indicated that chemical formation of N(2)O was not the main source of N(2)O during NH(4)(+) oxidation. After the addition of inhibitors of NH(4)(+) oxidation the soils contained NO(3)(−), but no N(2)O was produced. The results suggest that enhanced autotrophic NH(4)(+) oxidation is a potential source of N(2)O in fertilized acid forest soil.